Arabic version of pharmacy survey on patient safety culture: Hospital pharmacy settings. (September 2020) - Abdallah, Wael; Johnson, Craig; Nitzl, Christian; Mohammed, Mohammed Amin
Objective: The objective was to assess the validity and reliability of a translated Arabic language version of the pharmacy survey on patient safety culture released by the United States Agency for Healthcare Research and Quality in 2012 and to utilize this to assess staff attitudes and perceptions of the patient safety culture in hospital pharmacies of Kuwait. Methods: This study used a cross-sectional timeframe. Data were gained from three of the largest public hospital pharmacies and three of the largest private hospital pharmacies in Kuwait. The primary and secondary outcome measures were descriptive statistics, internal consistency, construct validity, model fit, and calculation of the positive response rate for all composites and items. Results: The results demonstrated that 9 of the 11 composites had a Cronbach's alpha (α) of >0.7, and all composites had factor loadings above 0.6. The standardized root mean residual score appropriately fitted the data with a value of 0.072. The intercorrelations among the patient safety composites ranged from 0.29 to 0.83. The proportion of pharmacy staff who categorized the grade of patient safety as "Good, " Very good, " or "Excellent" was 93%. Conclusion: The Arabic version of the pharmacy survey on patient safety culture questionnaire indicated suitable levels of reliability and validity. Also, the results demonstrated that the pharmacy staff surveyed in Kuwait have a positive perception of patient safety culture in their organizations.